Long-Term Strength Calculation of Flash Pile Structures on Heterogeneous Bases Including Weak Soils - Abdirahim, Madatov; Mastura, Khamidova (European Journal of Life Safety and Stability (2660-9630), 2022)
The article substantiates the accepted design scheme of a pile structure of an overpass type on inhomogeneous bases, including weak soils. The developed method of calculating the long-term strength of overpass pile structures on heterogeneous bases, including weak soils, is presented.